Problems of Legal Implementation of the Criminal Offense of Spreading Fake News and Hate Speech in Papua - Budiyanto, Budiyanto; Masum, Ahmad; Aidonojie, Paul Atagamen; Aslan, Jamal (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2024)
Social media users throughout the world are growing rapidly, to the point where they can cause commotion in society, in this case the state is present to overcome the commotion that occurs through a set of special regulations regarding the spread of fake news and hate speech. However, in law enforcement practices, specifically at the Papua Regional Police, there is still misleading between the limits of freedom of opinion and the offense of spreading fake news and hate speech. This research will analyze the strict limits in law enforcement regarding the criminal offense of spreading fake news and hate speech with freedom of expression in Papua. This research uses normative juridical research methods. The research results show that the problem of spreading fake news and hate speech in Indonesia has been regulated in various regulations, but its implementation still does not provide a sense of justice for victims. Judges' sentences tend to be lower than the demands, so the perpetrator's sentence is still too light. Especially related to actions that cause riots or conflict in Papua. So regarding the offense of spreading fake news and hate speech, it is important to reformulate the formulation regarding prohibited acts, criminal liability, types of punishment, and forms of legal settlement. Special minimum sentences need to be clearly regulated for criminal acts that have an impact on conflict and unrest, such as the crime of spreading fake news and hate speech.